A A corpus-based study on the use of cohesive devices in the lesson plans of pre-service teachers - Ronlie RJ Espeleta (Universidade Estadual de Alagoas, 2024)
This study explores the use of cohesive devices in lesson plans (LPs) prepared by pre-service teachers across various subjects, specifically focusing on English, Math, and Biology majorships in a state university in the Philippines. The research highlights the prevalent use of personal references among English pre-service teachers, who favor the word "you" for its role in maintaining a second- and third-person perspective. In contrast, Math and Biology pre-service teachers predominantly employ nominal substitutions and conjunctions to enhance coherence in their LPs. The study also notes the absence of ellipsis in the analyzed LPs and identifies the predominant use of nominal substitution and extension conjunctions across subjects. By comparing the frequency and types of cohesive devices used, the research underscores the variations in linguistic strategies employed by pre-service teachers of different disciplines. The findings suggest a need for greater awareness and training on the effective use of cohesive devices to improve lesson planning and instructional clarity.